2023
DOI: 10.3390/ani13030393
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Fermentation of Plant Feedstuff Mixture Affected the Physiological Responses of European Seabass (Dicentrarchus labrax) Reared at Different Temperatures and Subjected to Salinity Oscillation

Abstract: This study aimed to evaluate the effects of dietary inclusion of plant feedstuff mixture (PFM) pre-treated by solid-state fermentation (SSF) on the physiological responses of European seabass. For that purpose, two diets were formulated to contain: 20% inclusion level of non-fermented plant ingredients mixture (20Mix) and 20Mix fermented by A. niger in SSF conditions (20Mix-SSF). Seabass juveniles (initial body weight: 20.9 ± 3.3 g) were fed the experimental diets, reared at two different temperatures (21 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…A solution uses biological strategies that degrade these compounds, such as solid-state fermentation (SSF), which involves the microbial fermentation of a substrate where subsequent by-products may provide residual bioactive components [114]. Amaral et al (2023) evaluated the effect of SSF on plant feedstuff (soybean, rapeseed, sunflower, and rice bran) fermented with Aspergillus niger in stressed European Seabass (Dicentrarchus labrax). However, the results of fish-fed test diets subjected to different temperatures and salinity oscillation indicated that fermented products did not mitigate the impact of environmental stress [128].…”
Section: Non-conventional Plant Mealmentioning
confidence: 99%
See 1 more Smart Citation
“…A solution uses biological strategies that degrade these compounds, such as solid-state fermentation (SSF), which involves the microbial fermentation of a substrate where subsequent by-products may provide residual bioactive components [114]. Amaral et al (2023) evaluated the effect of SSF on plant feedstuff (soybean, rapeseed, sunflower, and rice bran) fermented with Aspergillus niger in stressed European Seabass (Dicentrarchus labrax). However, the results of fish-fed test diets subjected to different temperatures and salinity oscillation indicated that fermented products did not mitigate the impact of environmental stress [128].…”
Section: Non-conventional Plant Mealmentioning
confidence: 99%
“…Amaral et al (2023) evaluated the effect of SSF on plant feedstuff (soybean, rapeseed, sunflower, and rice bran) fermented with Aspergillus niger in stressed European Seabass (Dicentrarchus labrax). However, the results of fish-fed test diets subjected to different temperatures and salinity oscillation indicated that fermented products did not mitigate the impact of environmental stress [128].…”
Section: Non-conventional Plant Mealmentioning
confidence: 99%
“…The substrate was stirred daily to ensure proper substrate oxygenation due to the 5 cm height of the substrate bed, and the tray was covered with plastic film with small holes. After SSF, the fermented mixture was dried at 60 • C for 3 days [32].…”
Section: Solid-state Fermentationmentioning
confidence: 99%
“…There are already some reports describing the benefits of SSF for growth performance and feed efficiency [27][28][29], feed digestibility [30], feed palatability [31], innate immunity [32], and stress tolerance [33] in fish. To date, there is limited information on the effects of PF treated using SSF with A. niger on fish growth performance and feed digestibility.…”
Section: Introductionmentioning
confidence: 99%